Wireless signal uplink transmission on existing optical gigabit Ethernet links without using additional light source and baseband filtering - Ukrit Mankong (2018)
A Radio over Fiber uplink scheme is demonstrated experimentally where wireless signal is modulated on the same optical carrier as the existing optical Gigabit Ethernet link, taking advantage of prevalent Fiber to the Curb infrastructures. Without optical amplifier and filter, the received WLAN IEEE 802.11g signals show acceptable EVM up to 36 Mb/s over 8 km of fiber. The gigabit baseband signal does not require electrical filter and has power penalty below 0.5 dB at BER 10-10 in the presence of wireless signal with optimal powers. This method optimizes the fiber resources and can also be applied to other wireless signals. © 2011 IEEE.